Variasi Metode Pembelaran Sejarah Kebudayaan Islam (SKI) di MTS Miftahul Ulum Weding Bonang Demak - Rifriyanti, Eni (Universitas Islam Sultan Agung, 2019)
The main problem in this research is how the implementation of strategy of the teacherÂ in selectif the method variation on the learning of SKI in MTs. Miftahul Ulum Weding Bonang Demak and how is the positive response of learners to the variation of methods on learning SKI in MTs. Miftahul Ulum Weding Bonang Demak.The method used in this study is a qualitative method, data collection techniques used by researchers are interviews, observation, and documentation.The result s of this study are: 1) there are variations of strategy used by the teacher on learning SKI in MTs. Miftahul Ulum, the consideration of using strategies are: the healt condition of learners; the psychological condition of learners; the scheduled time for SKI subjects;the contens of the SKI lesson material to be delivered. 2) positive response of learners to the variation of methods on learning SKI in MTs. Miftahul Ulum is shown by the spirit of learning when the lesson of SKI is delivered by using variation of learning method, the learners are not sleepy when subjects of SKI are delivered with varied method, they feel good and not bored when SKI lesson is presented by using varied method, lacking of the subject of SKI organized by the school, and felt the need to add additional hours of SKI subject.Â Keywords: method variation, learning SKI